Manufacturing process design and optimization - Rhyder, Robert F (Manufacturing engineering and materials processing, 1997)
Stressing the paradigms of improvement and emphasizing the hands-on use of the tools furnished, Manufacturing Process Design and Optimization explains process components and examines system architecture...shows how process paths are formed and how to calculate paths in both simple and complex systems...introduces methods to minimize the formation of paths in process design and process optimization...offers a nonmathematical approach to designed experiments...reviews both Western design methods and Taguchi concepts...supplies preformatted response tables for the analysis of experimental results...and more.